Acción reductora del extracto etanólico de Zingiber officinale Roscoe (jengibre) sobre el ión férrico - Blas Vásquez, Silvia Yanet (2017)
The present work of investigation is oriented to the determination of the reducing action of the ethanolic extract of Zingiber officinale Roscoe (ginger) on the ferric ion, using as standard gallic acid. Ethanolic extracts were prepared at concentrations of 31.45, 15.73, 7.86, 3.93 and 1.96 mg / mL by mixing with potassium ferricyanide. The phenolic compounds present in the rhizome samples reacted with the ferric ion, in such a way that they developed a blue-green coloration; of these systems the reading of absorbance at 700 nm was performed, indicating that the increased absorbance of the mixture gives an increase in reducing power. The in vitro reducing power was expressed as relative percentages, being the one of greater concentration, greater this percentage. The ethanolic extract of the rhizome Zingiber officinale Roscoe (ginger) has a reducing action against the ferric ion and in addition the maximum relative percentage of reducing power of the ethanolic extract of the rhizome Zingiber officinale Roscoe (ginger) on the ferric ion was of 6.5%.